Factors influencing oral output of foreign language learners in the teaching of Chinese as a foreign language: a case study / Bok Check Meng, Afidah Bidin and Goh Ying Soon - Bok, Check Meng; Bidin, Afidah; Goh, Ying Soon (Akademi Pengajian Bahasa, 2021)
Globalisation has increases the need for us to speak a common language. The overwhelming growth of Chinese use in different countries and the possibility of online use of the language have allowed by the need to communicate in Chinese with Chinese speakers from other countries that speak Chinese, creating a new learning context for oral output. In this case study, qualitative analysis were conducted to identify how the process of oral out and communication occur through a qualitative research design. For that purpose, observations, analysis of the oral output during online discussions using Flipgrid, interviews with the students were done as assessment of their communicative skills. The results show the importance of the communication in the interaction in group and within the Flipgrid community, the influence of the social context and inside the Flipgrid community and the intrinsic motivation due to the use value of learning in a pluricultural and communication context. The findings will also help the learners to develop self-confidence and to combat speaking anxiety. Further recommendations and suggestions are discussed in this study.